The Analysis Implementation of Character Building Attentiveness and Sensitivity based on Character First Education - Putri Wulan Agustina; Khusnul Fajriyah; agenes lita; Agnita Siska Pramasdyahsari (Jurnal Cakrawala Pendas, 2024)
Character education is now the main focus of experts and educational institutions. Character is formed from small actions that are repeated until they become habits. To be effective, character education must be applicable and easy to understand so that students and their environment can feel the benefits. This study aims to describe and analyze the implementation of character building at SD Bukit Aksara Semarang City. The research method used a qualitative approach with naturalistic inquiry, and the subjects were grade 4 students. Data were collected through observation, interviews, documentation, and literature review. Data validity was obtained through confirmation of results and triangulation. The results showed that the implementation of character building at SD Bukit Aksara Semarang City is as follows: 1) The implementation of character building has been carried out through curriculum programs integrated with character-first education at each grade level and structured in the semester program. 2) In grade 4, the character values emphasized are attentiveness and sensitivity with indicators listed. 3) The implementation of character building is often inserted during the learning process in class, especially project-based learning, which is the school's semester program. The character of attentiveness and sensitivity is an essential aspect of character education that focuses on developing students' personalities. The impact is that students can understand and feel what others are experiencing, improve social skills, encourage responsibility, and help create a positive learning environment. Overall, the implementation of character building at SD Bukit Aksara has shown significant success, but a more holistic approach involving the family and social environment is still needed. Given the influence of external factors not described in this study, further research is required to understand how the environment outside school affects the development of students' attentiveness and sensitivity character and how appropriate solutions can be implemented to overcome these obstacles.